Software Sustainability Institute 2023 Fellowship Application - Ahmad, Umar Salisu (My University, 2022)
This is the application for Software Sustainability Institute 2023 Fellowship Application. I explained my plans for the fellowship as follows: To develop bioinformatics and computational genomics course To develop short courses in areas of data science using R & Python To develop short training modules about preprints and open science, I would like to be part of the SSI fellowship because the SSI community highly compliments my own goals and passion to promote Open Science and develop the capacity of our local scientists, computationally.
Keywords: Software Sustainability Institute; Open Science; Computational genomics